Multiply to simplify the polynomial expression (r - 1) (r2 - 2r+3).

1 answer

To simplify the expression \((r - 1)(r^2 - 2r + 3)\), we can use the distributive property (also known as the FOIL method for binomials). We will distribute \(r - 1\) to each term in the trinomial \(r^2 - 2r + 3\):

  1. Start by distributing \(r\):

    • \(r \cdot r^2 = r^3\)
    • \(r \cdot (-2r) = -2r^2\)
    • \(r \cdot 3 = 3r\)
  2. Next, distribute \(-1\):

    • \(-1 \cdot r^2 = -r^2\)
    • \(-1 \cdot (-2r) = 2r\)
    • \(-1 \cdot 3 = -3\)

Now, combine all the terms together: \[ r^3 - 2r^2 + 3r - r^2 + 2r - 3 \]

Next, combine like terms:

  • The \(r^2\) terms: \(-2r^2 - r^2 = -3r^2\)
  • The \(r\) terms: \(3r + 2r = 5r\)

Thus, putting it all together, we have: \[ r^3 - 3r^2 + 5r - 3 \]

Therefore, the simplified polynomial expression is: \[ \boxed{r^3 - 3r^2 + 5r - 3} \]